সংবাদপত্রের সম্পাদকীয় নীতিমালা - রহমান, রাফিজা.; আক্তার, শাহেলা.; Mass-Line Media Center (Dhaka, Bangladesh) (ঢাকা : মাস-লাইন মিডিয়া, 2002)
Contributed articles on social perspectives of mass media and adequacy of press coverage in Bangladesh; edited papers of various seminars.
In Bengali.
Keywords: Technical writing; Editing -- Handbooks, manuals, etc